Color stability of highly filled composite resin materials for facings - Stober, Thomas; Gilde, Herbert; Lenz, Peter (Dental materials, 2001)
The aim of the investigation was to examine the color stability of seven resin-based facing composites with a high content of inorganic filling material (Colombus, Artglass, Sinfony, Targis, Zeta LC, Zeta HC, BelleGlass HP/dentine, BelleGlass HP/enamel).
Available online 19 December 2000
Gesehen am 16.02.2021